PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS (Studi pada Perusahaan Sub Sektor Food and Beverage di BEI periode 2013-2017) - Ariefa Pranadhani; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2019)
This study aimed to analyzed the effects of working capital turnover, account receivable turnover, and firm size on profitability. This study uses secondary data from the annual report by Indonesia stock exchange, the population in this study include 16 sub sector of food and beverage enterprises listed in Indonesia Stock Exchange period of 2013-2017. Sample of this study consist of 12 food and beverage enterprises that meet all the criteria. The analysis used is linear regression analysis with SPSS 23 version application program. Regression analysis showed that, in partial, working capital turnover, account receivable turnover, and firm size has a positive and significant effect on profitability. In simultan, working capital turnover, account receivable turnover, and firm size has a significant effect on profitability. Next, based on the results of multiple analysis, working capital turnover is a variable that has a dominant influence on proftiability. As analysis showed that value of beta coefficient (β) is 0.359,  account receivable turnover 0.278, and firm size 0,213.